(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The research aimed to identify the most important requirements for administrative empowerment in the first stage of basic education schools from the point of view of the educational mentors, The differences in the estimates of educational counselors are defined according to the following variables: academic qualification, years of experience, training courses. To achieve the objectives of the study, the researcher adopted the descriptive approach, and used a questionnaire consisting of (30) items, Where the study sample consisted of (66) educational directors. The study revealed the following results: 1- There are no statistically significant differences in the educational supervisors’ estimates of empowerment requirements due to the variable of academic and educational qualifications in the areas of organizational and logistical requirements, and the presence of significant and significant differences in the field of administrative requirements in favor of the graduate studies campaign.. 2-There are no statistically significant differences in the educational supervisors’ estimates of the administrative empowerment requirements in the first cycle schools due to the variable number of years of experience in the field of logistical requirements, while there were differences in relation to the administrative and organizational requirements. 3-There are no statistically significant differences in the educational supervisors’ estimates of the administrative empowerment requirements in the first cycle schools due to the variable of training courses.